Syntheses of 3-[(Alkylamino)methylene]-6-methyl-1Hpyridine-2,4-diones, Fluorescence Probes 3-Substituted 7-Methyl-6H-pyrano[3,2-c]pyridine-2,5-diones, and Tetrahydro-6H-2,10-dioxa-9-azaanthracen-1-ones - Prior, Allan M.; Gunaratna, Medha J.; Kikuchi, Daisuke; Desper, John; Kim, Yunjeong; Chang, Kyeong-ok; Maezawa, Izumi; Jin, Lee-Way; Hua, Duy H. (My University, 2014)
Various condensation and ring-closing reactions were used for the syntheses of 3-[(alkylamino)methylene]-6-methylpyridine-2,4(1H,3H)-diones, bicyclic pyridinones, and tricyclic morpholinopyrones. For instance, 3-[(dialkylamino)methylene]-6-methylpyridine-2,4(1H,3H)-diones were synthesized from the condensation of dialkylamines and 3-formyl-4-hydroxy-6-methylpyridin-2(1H)-one. 3-Formyl-4-hydroxy-6-methylpyridin-2(1H)-one, derived from 3-formyl-4-hydroxy-6-methylpyridin-2(1H)-one, was used to construct a number of bicyclic pyridinones via a one-pot Knoevenagal and intramolecular lactonization reaction. Tricyclic morpholinopyrones were assembled from a dialkylation reaction involving a dinucleophile, 3-amino-4-hydroxy-6-methyl-2H-pyran-2-one, and a dielectrophile, trans-3,6-dibromocyclohexene. Depending on the reaction conditions, isomers of the tricyclic molecules can be selectively produced, and their chemical structures were unequivocally determined using single-crystal X-ray analyses and 2D COSY spectroscopy. The fluorescently active bicyclic pyridinone compounds show longer absorption (368–430 nm; maximum) and emission wavelengths (450–467 nm) than those of 7-amino-4-methylcoumarin (AMC; λ[subscript abs,max] = 350 nm; λ[subscript em] = 430 nm) suggesting these molecules, such as 3-(2-aminoacetyl)-7-methyl-2H-pyrano[3,2-c]pyridine-2,5(6H)-dione, can be employed as fluorescence activity based probes for tracing biological pathways.
Keywords: Dialkylation; Fluorescence probes; Heterocycles; 3- substituted 7-methyl-6H-pyrano[3,2-c]pyridine-2,5-diones; tetrahydro-6H-2,10-dioxa-9-azaanthracen-1-ones